GCK exonic mutations induce abnormal biochemical activities and result in GCK-MODY - Dai, Tongtong; Yang, Yun; Zhang, Juanjuan; Ma, Xiaoyu; Chen, Lifen; Zhang, Caiping; Lv, Sheng; Li, Lin; Tang, Renqiao; Zhen, Ni; Lu, Wenli; Li, Chuanyin; et al. (Frontiers in Genetics, 2023)
Objective: Glucokinase-maturity-onset diabetes of the young (GCK-MODY; MODY2) is a rare genetic disorder caused by mutations in the glucokinase (GCK) gene. It is often under- or misdiagnosed in clinical practice, but correct diagnosis can be facilitated by genetic testing. In this study, we examined the genes of three patients diagnosed with GCK-MODY and tested their biochemical properties, such as protein stability and half-life, to explore the function of the mutant proteins and identify the pathogenic mechanism of GCK-MODY. Methods: Three patients with increased blood glucose levels were diagnosed with MODY2 according to the diagnostic guidelines of GCK-MODY proposed by the International Society for Pediatric and Adolescent Diabetes (ISPAD) in 2018. Next-generation sequencing (whole exome detection) was performed to detect gene mutations. The GCK gene and its mutations were introduced into the pCDNA3.0 and pGEX-4T-1 vectors. Following protein purification, enzyme activity assay, and protein immunoblotting, the thermal stability and enzyme activity of GCK was determined, along with the ubiquitination level of the mutant GCK protein. Results: Genetic testing revealed three mutations in the GCK gene of the three patients, including c.574C>T (p.R192W), c.758G>A (p.C253Y), and c.794G>A (p.G265D). The biochemical characteristics of the protein encoded by wild-type GCK and mutant GCK were significantly different; compared to wild-type GCK, the enzyme activity encoded by the mutant GCK was significantly reduced, suggesting thermal instability of the mutant GST-GCK. The protein stability and expression levels of the mutant GCK were significantly reduced, and the enzyme activity of GCK was negatively correlated with the levels of fasting blood glucose and HbA1c. In addition, ubiquitination of the mutant GCK protein was higher than that of the wild-type, suggesting a higher degradation rate of mutant GCK than WT-GCK. Conclusions: GCK mutations lead to significant changes in the biochemical characteristics of its encoded proteins. The enzyme activities, protein expression, and protein stability of GCK may be significantly reduced in patients with GCK gene mutations, which further causes glucose metabolism disorders and induces MODY2.